Food Supply Strategies in the Romanian Eneolithic: Sheep/Goat Husbandry and Fishing Activities from Hârşova Tell and Borduşani-Popină (5th Millennium BC). (2014) - Bréhard, Stéphanie; Radu, Valentin; Martin, Alexis; Hanot, Pauline; Popovici, Dragomir; Bălăşescu, Adrian
Abstract : Previously observed specialization in sheep/goat kill-off patterns from Romanian Eneolithic sites raises the question of a limited duration of the slaughtering period. In order to provide reliable month of death distribution for sheep/goats, the approach developed here takes into account uncertainties regarding the age-at-death and the month of birth, based on classic archaeozoological techniques. We show that sheep slaughtering rarely occurred from late spring to early autumn or from summer to mid-fall, both at Hârşova tell and Borduşani-Popină. Conversely, it is very likely that fishing activities took place primarily from spring to early autumn. This points to the existence of seasonal and complementary food supply strategies at both sites. Several possible explanations for these seasonal strategies are discussed. We also highlight the homogeneity in the management of domestic herds between the two sites, raising the question of a certain standardization in pastoral practices on a larger scale.